Highly Integrated Single-Base Resolution Maps of the Epigenome in Arabidopsis - Lister, Ryan (2008)
Deciphering the multiple layers of epigenetic regulation that control transcription is critical to under-standing how plants develop and respond to their environment. Using sequencing-by-synthesis technology we directly sequenced the cytosine methylome (methylC-seq), transcriptome (mRNA-seq), and small RNA transcriptome (smRNA-seq) to generate highly integrated epigenome maps for wild-type Arabidopsis thaliana and mutants defective in DNA methyltransferase or demethylase activity. At single-base resolution we discovered extensive, previously undetected DNA methylation, identified the context and level of methylation at each site, and observed local sequence effects upon methylation state. Deep sequencing of smRNAs revealed a direct relationship between the location of smRNAs and DNA methylation, perturbation of smRNA biogenesis upon loss of CpG DNA methylation, and a tendency for smRNAs to direct strand-specific DNA methylation in regions of RNA-DNA homology. Finally, strand-specific mRNA-seq revealed altered transcript abundance of hundreds of genes, transposons, and unannotated intergenic transcripts upon modification of the DNA methylation state.